E-080 Gender characteristics, comorbidity and outcomes of cerebral venous sinus thrombosis in a novel u.s. population. (22nd July 2019) - Walsh-Blackmore, S; Fraser, J; Kitzman, P; Dobbs, M
Abstract : Introduction: Cerebral Venous Sinus Thrombosis (CVST) has an estimated incidence of 1.32–1.57/100, 000/yr, with death or severe disability in less than 10%. There is a reported elevated incidence in young -middle age females. The majority of reported epidemiologic and outcome data has been collected outside the United States (US). Available US data shows low representation of the Appalachian region, which has relatively a higher burden of disease and lower socioeconomic level. The objective of this study was to examine the gender characteristics of CVST patients in the United States, with greater representation of the Appalachian region. Methods: Data were collected in a retrospective cohort using the Kentucky Appalachian Stroke Registry (KApSR), collected from admissions in a Comprehensive Stroke Center serving 554, 300 from the central-eastern United States. All diagnosed CVST patients found in the database from 2010–2018 greater than 18 years of age were included in the data set. Descriptive data were computed using SPSS statistics. Results: 101 patients diagnosed with CVST were included. 58 patients were female (57.4%). Median age was 44 years. The National Institutes of Health Stoke Scale (NIHSS) was reported for 32 female and 21 male patients. Median NIHSS was.5 in females and 0 in males at admission. Median length of stay was 7 days in females vs. 4 days in males. Discharge data were available for 51 female and 33 Male patients. Of female patients, 28 (55%) were discharged to home, 17(33%) were transferred to continued care, 4(8%) were transferred to hospice and 2(4%) died within 48 hours of admission. Of male patients, 25(76%) were discharged to home, 7 (21%) were transferred to continued care, and 1 (3%) was transferred to hospice. Female patients had a higher burden or comorbidities and multimorbidity compared to male patients. Conclusion: The results of this study indicate a higher burden of comorbidity, more severe presentation, and worse prognosis in female patients. This is in contrast to the majority of CVST research, many of which have found the male sex to be an independent risk factor for worse outcomes. This may reflect a particular variant among the Appalachian population Disclosures: S. Walsh-Blackmore: 1; C; University of Kentucky Center for Clnical and Translational Sciences Professional Student Mentored Research Fellowship. J. Fraser: None. P. Kitzman: None. M. Dobbs: None.